2007
DOI: 10.1007/s11240-007-9301-9
|View full text |Cite
|
Sign up to set email alerts
|

Seed specific expression of perilla γ-tocopherol methyltransferase gene increases α-tocopherol content in transgenic perilla (Perilla frutescens)

Abstract: Increasing vitamin E activity in economically important oil crops such as perilla will enhance the nutritional value of these crops. Perilla (Perilla frutescens Britt) represents an important oil crop in Asian countries, including Korea. Using Agrobacterium-mediated transformation, we have engineered perilla with the c-tocopherol methyltransferase (c-TMT) gene under the control of seed-specific vicillin promoter. Molecular characterization including PCR, Southern and Northern blots confirmed that the c-TMT tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…So far, the γ-TMT gene has been cloned from Arabidopsis thaliana, Brassica napus, Triticum aestivum, Helianthus annuus, and many other plants. The overexpression of the γ-TMT gene (mostly from A. thaliana) has been reported in Perilla frutescens, Lactuca sativa, Brassica juncea, Codonopsis lanceolata, and in soybean seed (Van Eenennaam et al, 2003;Cho et al, 2005;Yusuf and Sarin, 2007;Lee et al, 2008;Seong et al, 2009), which demonstrated the increase of α-tocopherol. In this study, the gene encoding γ-tocopherol methyltransferase, LsTMT, was cloned from L. sativa for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the γ-TMT gene has been cloned from Arabidopsis thaliana, Brassica napus, Triticum aestivum, Helianthus annuus, and many other plants. The overexpression of the γ-TMT gene (mostly from A. thaliana) has been reported in Perilla frutescens, Lactuca sativa, Brassica juncea, Codonopsis lanceolata, and in soybean seed (Van Eenennaam et al, 2003;Cho et al, 2005;Yusuf and Sarin, 2007;Lee et al, 2008;Seong et al, 2009), which demonstrated the increase of α-tocopherol. In this study, the gene encoding γ-tocopherol methyltransferase, LsTMT, was cloned from L. sativa for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…While g-tocopherol dominated the tocopherol composition of wild-type seeds (>95%), a-tocopherol represented up to 95% of seed tocopherols in the best transgenic event [23]. Subsequently, the successful conversion of g-tocopherol into a-tocopherol via g-TMT overexpression has been reported in many other plants including soybean [24][25][26][27], shiso [28], lettuce [29], mustard [30], maize [31], and tobacco [32]. Because of the higher biological activity of a-tocopherol, most g-TMT overexpressing crops exhibited 5-10 times higher vitamin E activity than untransformed plants.…”
Section: Update On the Tocochromanol Biosynthetic Pathwaymentioning
confidence: 99%
“…일반적으로 tocopherol 이성체는 α > β > γ > δ-isomer의 순으로 항산화 능력이 평가되었다 (Haung et al, 1994). Lee et al (2008) 계열의 유지를 혼합하여 ω-6/ω-3 비율을 조절하여 들깨유의 취약성을 개선할 수 있을 것으로 보인다 (Kim et al, 1996;Kim et al, 1999b;Lee et al, 2012). …”
Section: 기능성 유지자원의 개발unclassified